2000
DOI: 10.1530/eje.0.1430273
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo effects of beta-3-receptor agonist CGP-12177 on thyroxine deiodination in cold-exposed, sympathectomized rat brown fat

Abstract: Objective: The effects of the beta-3-receptor agonist CGP-12177 on thyroxine (T4) deiodination in sympathectomized (SX) interscapular brown adipose tissue (BAT) were assessed in 300 g body weight (BW) Wistar rats. Design: Seven days after SX, groups of rats were implanted s.c. with pellets containing 5 mg CGP-12177 or 5 mg norepinephrine (NE) and were immediately placed at 4 8C for 24 h. Other SX groups were injected with CGP-12177 or NE 1 mg/kg BW i.p. and placed in the cold for 4 h. The latter group was inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Numerous complex phenomena take place in BAT after exposure to low temperatures, leading to the synthesis of mitochondrial proteins involved in heat production. A critical role in this process is the synthesis of uncoupling protein-1 (UCP-1), strongly promoted by norepinephrine (NE) through a synergism between ␣-and ␤-adrenergic receptors (24,32,40). The presence of the thyroid hormones is essential to initiate BAT heat production, because triiodothyronine (T 3 ) potentiates the action of NE on UCP-1 gene transcription (2-4, 37).…”
mentioning
confidence: 99%
“…Numerous complex phenomena take place in BAT after exposure to low temperatures, leading to the synthesis of mitochondrial proteins involved in heat production. A critical role in this process is the synthesis of uncoupling protein-1 (UCP-1), strongly promoted by norepinephrine (NE) through a synergism between ␣-and ␤-adrenergic receptors (24,32,40). The presence of the thyroid hormones is essential to initiate BAT heat production, because triiodothyronine (T 3 ) potentiates the action of NE on UCP-1 gene transcription (2-4, 37).…”
mentioning
confidence: 99%
“…A recent study [102] has demonstrated the unexpected presence of TSH receptors in human abdominal WAT although their functional relevance here is not yet understood. The SNS not only influences the tissue effects of thyroid hormones via effects on the de-iodination of T4 to the more potent T3 [103,104] but also by modifica-tion of the effects of thyroid hormones on mRNA transcriptional activity, at least in rodent BAT [1051. Conversely, thyroid hormones can regulate adenyl cyclase activity in rodent BAT [106] and a state of hypothyroidism leads to differential Il-adrenoceptor expression as well as post-receptor effects in both the brown and white AT of rats [107].…”
Section: Human Studies-limitations and Resultsmentioning
confidence: 99%